2023
DOI: 10.3390/pathogens12020333
|View full text |Cite
|
Sign up to set email alerts
|

Plant-Derived Products with Therapeutic Potential against Gastrointestinal Bacteria

Abstract: The rising burden of antimicrobial resistance and increasing infectious disease outbreaks, including the recent COVID-19 pandemic, has led to a growing demand for the development of natural products as a valuable source of leading medicinal compounds. There is a wide variety of active constituents found in plants, making them an excellent source of antimicrobial agents with therapeutic potential as alternatives or potentiators of antibiotics. The structural diversity of phytochemicals enables them to act throu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 167 publications
0
5
0
1
Order By: Relevance
“…Berberine is an isoquinoline alkaloid present in many species from the genera Berberis, Mahonia and Coptis. In Asia, berberine hydrochloride tablets are sold for the treatment of intestinal infectious diseases and diarrhea [53]. The study [54] found that cell growth from C. difficile spores was completely inhibited at berberine concentrations of 640 mg/L.…”
Section: Rootmentioning
confidence: 99%
See 1 more Smart Citation
“…Berberine is an isoquinoline alkaloid present in many species from the genera Berberis, Mahonia and Coptis. In Asia, berberine hydrochloride tablets are sold for the treatment of intestinal infectious diseases and diarrhea [53]. The study [54] found that cell growth from C. difficile spores was completely inhibited at berberine concentrations of 640 mg/L.…”
Section: Rootmentioning
confidence: 99%
“…Plants are an inexhaustible source of bioactive substances. As there are approximately 500,000 plant species exist on the planet, of which only 1% has been phytochemically investigated [8]. Among medicines prescribed in the USA, 25% is based on compounds isolated from plants [9].…”
Section: Introductionmentioning
confidence: 99%
“…Bronchopulmonology, otorhinolaryngology свидетельствовало о выраженном антимикробном эффекте композиции масел «Дыши». Как известно, существуют тысячи структурно различных соединений, производимых растениями (полифенолы, терпеноиды, фенольные кислоты, эфирные масла, лектины, полипептиды и алкалоиды), каждое из которых обладает различными биологическими свой ствами, которые обеспечивают в т. ч. и антимикробные свой ства [20]. Разрушение плазматической мембраны является наиболее распространенным механизмом противомикробного действия ЭМ.…”
Section: результаты и обсуждениеunclassified
“…Medicinal plants are a storehouse of numerous bioactive compounds with various therapeutic properties. The therapeutic potential of plants has been well explored over a very long period (Qassadi et al, 2023). The vast array of therapeutic effects associated with medicinal plants includes anti-inflammatory, antiviral, antitumor, antimalarial, and analgesic (Raina et al, 2014).…”
Section: Introductionmentioning
confidence: 99%